Proud day for Kedahans: Installation of Tuanku Abdul Halim as King a special moment for many - The, Star (The Star, 2012)
ALOR SETAR : Forty-two years ago, Rosmawati Abu Bakar was an excited little girl who watched the Sultan, Tuanku Abdul Halim Mu'adzam Shah, ascending the throne as King.